A qualitative study to explore relatives’ and family carers’ perspectives of the ‘move into a care home’ - Hunt, Emma (2011)
This qualitative study, aims to i) explore the process of ‘moving into a care home’ from the perspectives of relatives/family carers and ii) identify the needs of relatives/family carers throughout the process of ‘moving to a care home’. With Britain’s ageing population, people are more likely to need to move into a care home. The move can lead to psychological distress as well as poor integration of the older person and their families into the care home environment. Recent policy has focussed on avoiding admission to a care home where possible, rather than meeting the needs of people for whom it is the only option. Data were collected using semi-structured interviews involving seven participants that had previously assisted a relative to move into a care home. Analysis revealed three themes relating to the process: ‘recognising the need’, ‘the decision-making process’ and ‘adapting caregivers’ roles’, and two themes relating to relatives/family carers needs: ‘support and information’ and ‘involvement in residents care’. The findings show that the process was smoother for relatives/family carers when there was early recognition of the need for a care home, and when families were involved in decision-making, however decisions were often found to be expert-driven. Support was noted as a key need for relatives/family carers, yet it was evident that healthcare professional’s (HCPs) need more training to provide appropriate support effectively. The study showed that the process of moving into a care home has a negative public image and until this is alleviated relatives/family carers will continue to resist the process.